Desenvolvimento e nutrição do capim-Tanzânia em função da aplicação de zinco - Hernandes, Amanda [UNESP]; De Mello Prado, Renato [UNESP]; De Souza Pereira, Fabiana [UNESP]; Moda, Leandro Rosatto [UNESP]; Dos Santos Ichinose, Juliana Garcia [UNESP]; De Cássia Melo Guimarães, Rita [UNESP] (My University, 2009)
It was aimed to assess the effects of zinc in the development and nutrition of Tanzania grass. The experimental design used was fully randomized, consisting of six doses of zinc (0, 15, 30, 60, 120 and 240 mg dm'3) and four repetitions. The experimental unit was formed in a vase filled with a Red Latosol dystrophic (Zn = 0.4 mg dm). There were two cuts, the first after 53 days of transplanting seedlings and the second 35 days after the first cut. Was evaluated the concentration of zinc in the soil, the content of zinc leaf, the number of tillers, number of leaves, plant height, the dry mass of the shoot, root system and the whole plant. The doses of zinc influenced the concentration of zinc in soil and plant, and production of dry mass of Tanzania grass, especially the first cut. The Tanzania grass shows high tolerance to the toxicity of zinc, and toxic critical level of 273 mg kg-1.
Development and nutrition of Tanzania grass in function the implementation of zinc
Keywords: Fertility; Micronutrient; Nutrition; Panicum maximum; Pasture; Soil